Iron nutrition of plants: an overview on the chemistry and physiology of its deficiency and toxicity - Fageria, Nand Kumar; Baligar, V. C.; Wright, R. J. (Pesquisa Agropecuaria Brasileira, 2014)
Iron deficiency and toxicity are important yield limiting factors in crop production around the world. In this review, an attempt is made to summarize the information on diagnosis of Fe deficiency and toxicity, chemistry of Fe in soil, mechanism of Fe uptake, role of chelates in Fe nutrition, factors affecting Fe availability to crop plants and measures required to correct Fe deficiency and toxicity. A brief discussion about Fe toxicity in flooded rice is also included. Information presented in this review article should provide a basis for correcting this nutritional disorder in crop plants, and indicates new research efforts needed to solve Fe stress problems.